Protective autophagy alleviates neurotoxin-gelsenicine induced apoptosis through PERK signaling pathway in Neuro-2a cells. (30th May 2022) - Li, Yujuan; Hu, Peipei; Zhang, Zhiqiang; Yuan, Zhihang; Yang, Kun; Sun, Zhiliang
Abstract: Gelsemium elegans Benth. ( G. elegans ) showed significant biological activities, but it has the side effects of neurotoxicity, predominantly in the form of respiratory depression. Gelsenicine is the main toxic constituent of G. elegans which is highly neurotoxic to humans and animals. Although the acute neurotoxicity of gelsenicine has been widely reported, but neurotoxicity mechanisms have not been elucidated and its direct effect on nerve cells remains poorly characterized. In this study, Neuro-2a cells were used to be our object of study for determining the mechanism by which gelsenicine induced neurotoxicity. We found that gelsenicine is neurotoxic to Neuro-2a cells; indeed cell proliferation was inhibited and apoptosis was induced in a dose-dependent manner. Meanwhile, gelsenicine markedly promoted autophagy and activated autophagic flux. Additionally, promoting autophagy with rapamycin decreased apoptosis, whereas blocking autophagy with 3-methyladenine (3-MA) increased apoptosis. Furthermore, the protein kinase ribose nucleic acid (RNA)-like endoplasmic reticulum kinase (PERK)/eukaryotic initiation factor 2 alpha (eIF2α)/activating transcription factor 4 (ATF4) signaling pathway was involved in the induction of protective autophagy in Neuro-2a cells. Inhibition of PERK using small interfering RNA (siRNA) inhibited gelsenicine-induced autophagy and aggravated apoptosis. These data indicate that gelsenicine not only exhibited cytotoxicity and induced apoptosis, but it also induced protective autophagy via PERK signaling pathway to alleviate gelsenicine-mediated apoptosis in Neuro-2a cells.